Bone mineral status in 134 patients with cystic fibrosis. Issue 3 (1st September 1999) - Laursen, E M; Mølgaard, C; Michaelsen, K F; Koch, C; Müller, J
Abstract : AIM: To investigate bone mineral status in patients with cystic fibrosis (CF). PATIENTS AND METHODS: Whole body bone mineral content (BMC), projected bone area, and bone mineral density (BMD) were determined by dual energy x ray absorptiometry in 134 patients with CF and compared with 396 healthy controls. RESULTS: In patients ⩽ 19 years of age, BMD for age was normal in boys and marginally reduced in girls, whereas BMC for age was significantly reduced in both sexes. Height for age and bone area for height were significantly reduced, indicating "short" and "narrow" bones, whereas BMC for bone area was increased, indicating increased size corrected BMC. In patients > 19 years of age, BMD and BMC for age were significantly reduced. CONCLUSION: Short and narrow bones were the main reasons for reduced BMC for age in patients ⩽ 19 years of age, indicating that treatment to prevent osteoporosis in younger patients should be directed at increasing bone size, whereas conventional treatment with calcium and vitamin D supplementation alone might not be as effective. Because of the significant decrease in BMD and BMC in adult patients, we fear that these patients may develop osteoporotic fractures prematurely.